Efektivitas Penggunaan Lie Detector Dalam Sistem Pembuktian Pidana Di Indonesia - Saputra, Gibran; Akli, Zul; Nurarafah, Nurarafah (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
The effectiveness of using lie detectors in the criminal evidence system in Indonesia is very dependent on the quality of the evidence. In this case, legal considerations need to be taken when using a lie detector to provide testimony in criminal cases. A lie detector can prove a criminal case that shows the suitability of the lie detector with other evidence as stated in Article 184 of the Criminal Procedure Code.The aim of this research is to determine the legal considerations regarding the use of lie detectors in the criminal evidence system in Indonesia and the effectiveness of the use of lie detectors in the criminal evidence system in Indonesia. This research uses a type of normative legal research using a statutory approach, a historical approach, and the nature of the research, namely analytical descriptive.The research results show that legal considerations regarding the use of lie detectors in the criminal evidence system in Indonesia are based on National Police Chief Regulation Number 10 of 2009. This regulation aims to increase scientific evidence in the criminal investigation process. Lie detectors are recognized as supporting evidence in accordance with the provisions stipulated in Article 184 of the Criminal Procedure Code and Article 5 Paragraph 2 of Law Number 19 of 2016, amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The effectiveness of the use of lie detectors in the criminal evidence system in Indonesia has four important factors in legal effectiveness. The use of lie detectors is in accordance with the law. Lie detectors are facilities that support law enforcement. Lie detectors are used in communities that understand technology and use. lie detectors are relevant to Indonesian culture.